KULINER KHAS KOTA TASIKMALAYA SEBAGAI KAJIAN MATERI DALAM MATA PELAJARAN SEJARAH JENJANG SMA - Armiyati, Laely; Fachrurozi, Miftahul Habib; Miftahudin, Zulpi; Sofiani, Yulia (Jurnal Pendidikan Sejarah Indonesia, 2024)
Culinary studies from a historical perspective present a picture of the social, cultural, and economic conditions of the local community. Culinary internalization in history subjects at the high school level is an effort to strengthen understanding of the connection between the past, present, and future. The research aims to trace the historical background of the typical cuisine of Tasikmalaya City and analyze the culinary integration strategy in the Senior High School. This research uses qualitative methods with a realist ethnographic approach through four phases, including 1) planning consists of determining the research setting, formulating research questions, and determining informants; 2) data collection includes observation, open interviews, and making ethnographic notes; 3) data analysis consists of content analysis and contextualizing the results of ethnographic notes with the high school history curriculum; and 4) report writing. The results show that the Tasikmalaya culinary specialties such as nasi tutug oncom (tutug oncom rice), bubur ayam (chicken noodle), bacang, baso noodle, rujak honje (honje salad), es sirop bojong (bojong ice), and soto, is closely related to the social, economic, and geographical life in Tasikmalaya. Tutug oncom rice is related to the difficult economic life of the community during the Japanese occupation. Chicken noodle, baso noodle, bacang, and soto illustrate the acculturation between Chinese and Sundanese cuisine. Sirop bojong ice characterizes the European influence on Tasikmalaya society as sirop was first introduced by the Dutch. Culinary integration in the history subjects is carried out by making relevance between the historical content of culinary existence and various concepts listed in the learning outcomes. Based on the results of the analyses and interviews, the culinary history content can be taught in Phase E of the Spice Route material and the relationship between the past, present, and future, as well as in Phase F of Class XI on the Japanese colonization material.